CRITICAL ANAESTHETIC INCIDENTS CAUSES AND ANALYSIS - Bajwa, Saleem Pervaiz; Abdullah, Dr.; Akram, Muhammad; Hussain, Akhtar; Safdar, C. Aqeel (Pakistan Armed Forces Medical Journal, 2019)
Objective: To improve the standard operating procedures (SOPs) for perioperative anesthesia management and reduction of complications where human error is involved.Study Design: Retrospective observational descriptive study.Place and Duration of Study: Department of Anesthesiam, Combined Military Hospital (CMH) Lahore, from Jun 2017 to Jun 2018.Material and Methods: Anesthesia related critical incidents were reported voluntarily in a proforma in this study. Results were then analyzed and audited for human errors, equipment malfunction, drug mishaps, patient factors, and nature of surgeries. Averages and percentage were calculated for these occurrences.Results: During one year 159 critical incidents (1.56%) were reported in 10181 patients. Airway and pulmonary incidents (49%), cardiovascular (42.1%) drug related (5%) and rare causes were (3.9%). Most incidents occurred during maintenance phase (40.88%), followed by emergence (25.16%), induction (23.27%) and post-operative period (10.69%). General anesthesia (1.56%), regional anesthesia (1.78%) and local anesthesia under monitored care (0.56%) were responsible for these adverse events. Analysis for reasons of these incidents suggested human errors (47.16%), patient’s comorbids (28.30%), nature of surgical procedures (24.52%) and combined factors were (71%). Anesthesia related mortality in our study was 5 deaths per 10000 anesthetics.Conclusion: Critical incidents do occur even in the hands of highly qualified and skilled anesthesiologists but can be minimized by continuous efforts through reporting and analysis of these events and hence formulating safety protocols.